SIEGE OF HALYCH IN 1387 IN THE LIGHT OF NATIVE HISTORIOGRAPHY - FEDORYK, Andrii (Halych. Scientific work collection, 2017)
The general historiography review of the question related to the siege of Halych by the Polish army and Lithuanian auxiliary detachments in 1387 is elucidated in this article. The attitudes of the representatives of different Ukrainian research schools at this key military event in the history of Halychyna, from the beginning of the first half of the ХІХ and to the beginning of the ХХІ century, are considered too. The author notes that the fact that Poland took over the capital of Halychyna from the Hungarian kingdom, found mainly very fugitive reflection in many scientific works, which can no longer satisfy the needs of modern historical science.